Interpretasi Tafsir Ekologi Dan Hakikat Kepemimpinan: Telaah QS. Ar-Rum : 41 menggunakan teori Maqashidu Syari’ah - Muhammad Farhan Akbar; M. Yunan Yusuf (Attractive : Innovative Education Journal, 2024)
The rise of the issue of environmental damage has become a global problem of concern, most of the causes come from human actions themselves. This study aims to examine the interpretation of Qs. Ar-Rum: 41 which explains the destruction of "fasad" on earth, this research will also examine the principles, meaning and nature of human leadership related to environmental issues based on the objectives of shariah. This research uses a qualitative method conducted by library research from the perspective of Ibn Katsir's interpretation. The results showed that the Maqashidu Shari'ah theory has ecological values that can be used as a basis in preserving the environment. Interpretation of ecological interpretation also has great significance in dealing with environmental problems based on the Holy Qur'an as the main guide. This can be the basis for the development of Islamic law that is more environmentally friendly and provides an in-depth understanding of ecological values in Islamic law contained in maqashidu shari'ah (the goals of shari'ah) including: hifz al-din, hifz al-nafs, hifz al-nasl, hifz al-'aql and hifz al-mal which have a connection with preserving the environment this indicates that the interpretation of ecology (environment) is contextual along with the times.